Evaluasi Pendidikan Islam: Prespektif Hadis Rasulullah SAW - Khairuddin bangun; Dwi Ratnasari (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2023)
This study aims to determine the Evaluation Of Islamic Education From The Perspective Of The Prophet Muhammad SAW. The author uses qualitative research methods in this study, using the type of library / library research and with a content analysis approach. Therefore, the authors collect hadiths related to educational evaluation. In this way, hadiths related to the evaluation of education will be found. In this research, the authors found the objectives, functions, principles, and types of evaluation of Islamic education according to the perspective of hadith. In this way, this writing will add to the treasures in Islamic education regarding the evaluation of Islamic education from the perspective of the hadith of the Prophet Muhammad.